(untitled) (Journal on Excellence in College Teaching, 2024)
This mixed-methods research study compared the level of community of inquiry (CoI) in online graduate classes that use web conferencing (WC) compared to those that do not. This study also investigated students’ perceptions of Teaching Presence (TP), Social Presence (SP), and Cognitive Presence (CP). The authors found that students had significantly higher (p < .001) levels of TP, SP, CP, and CoI in classes that used WC. The open comments reflected that students in classes using WC believed they had higher levels of community and recommended the use of WC in other classes.